Security Implications Of Election Ringing And Technology Use In The Twenty-First Century: Nigeria's 2015 Presidential Election From A Technological Standpoint - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The study looks at how elections in Nigeria and other countries set the stage for political succession. They once gave dishonest people and organizations the chance to carry out crimes of rigging to harm the electorate and other competitors. Stakeholders and the electorate are marginalized by unchecked manipulation, which results in their losing the election or having their votes stolen or canceled, all without their fault. This was the case prior to the introduction of smart card readers and permanent voter cards. The use of technology in Nigerian elections made it very difficult for results to be altered, either by dishonest people or by changing figures in an arbitrary and fraudulent manner. This electronic device is very difficult to copy or compromise due to its transparent application and built-in security mechanisms. Therefore, the purpose of this study is to examine the reasons why the smart card reader was necessary, the arguments against its usage, and its effectiveness in the 2015 presidential elections, as well as the possibility of more elections in the future.